Developing a Soil Test Extractant: The Correlation and Calibration Processes - George Hochmuth; Rao Mylavarapu; Ed Hanlon (EDIS, 2014)
An understanding of soil testing is an important part of preventing excess fertilizer applications that can potentially impact the environment and ensuring commercially viable yields and aesthetic, healthy landscapes. This 4-page fact sheet describes the process UF/IFAS soil scientists used to develop a predictive and/or diagnostic soil test that can be depended on by commercial agricultural and horticultural producers as well as homeowners and can provide accurate nutrient recommendations or diagnose nutrient imbalances for crops or plants. Written by George Hochmuth, Rao Mylavarapu, and Ed Hanlon, and published by the UF Department of Soil and Water Science, October 2014.